KEBUTUHAN PERAWATAN PENYAKIT PERIODONTAL DAN PERILAKU PEMELIHARAAN GIGI PADA MASYARAKAT DI KECAMATAN PANGURURAN SAMOSIR: PERIODONTAL TREATMENT NEED AND DENTAL HEALTH CARE BEHAVIOR IN SOCIETY OF PANGURURAN SAMOSIR - Simson Damanik; Josevina Silalahi (Dentika: Dental Journal, 2011)
Dental and oral health is the highet sixth complaint of the Indonesian people and was the most fourth ranked expensive treatment disease. The aim of this study was to know treatment need of periodontal disease and dental health care behavior. The type of research was a descriptive survey. CPITN index was used for assessing periodontal treatment need collecting data used interview assisted with questionnaire. The result showed that all respondents need periodontal treatment. Based on the highest periodontal score the percentage of calculus was the highest(73.57), followed by pocket 4-5 mm 19.3%, pocket > 6 mm 5.3%. A total of 75.77 respondents brushed their teeth twice a day, unfortunetly they brush their teeth while taking a bath. Based on the mean of CPITN sextan of, 5.2 sextands need professional scaling,0,1 sextant need comprehensive care and 0,3 need to improve oral hygien. In conlusion, most of the responden (75%) had calculus, pocket 4-5 mm 19.3%, and pocket > 6 mm 5.3%.